Survey-driven insights into the diversity and prevalence of nematode-fungus complex in guava - Rubal, K; Vinod, K; Sujata, K; Mann, S S; Deepak, K; Rohit, K; Parveen, K; Pawan, K; Harsh, C (Plant Science Today, 2026)
A systematic survey during 2022–2024 was conducted in guava orchards and nurseries of Jind, Hisar and Bhiwani districts in Haryana to assess the incidence, diversity and community structure of plant-parasitic nematodes (PPNs) and fungi associated with guava decline. A total of 150 samples of guava orchards were collected from Hisar, Jind and Bhiwani districts of Haryana, 105 were found infested with Meloidogyne incognita with a 70.0 % frequency of occurrence. Among 105 samples, 88 were found infested with M. incognita and Fusarium oxysporum f.sp. psidii both with a disease incidence of 58.6 % during 2022–24. In guava nurseries, 44 samples (out of 60) were infected with M. incognita having a frequency of occurrence of 73.0 % and 27 were infected with nematode and fungus (45.0 %). Results revealed that M. incognita and F. oxysporum f.sp. psidii were identified as the most prominent pathogens causing guava decline. Community analysis confirmed M. incognita as the most frequent and dominant nematode species, with relative frequencies up to 24.6 % and densities up to 60.2 %, followed by Helicotylenchus and Hoplolaimus. Morphometric observations of M. incognita obtained from the current study were similar to those of its original description. Morphological identification of the fungus associated with guava decline was identified as F. oxysporum f.sp. psidii . The results revealed a strong association between M. incognita and F. oxysporum, contributing to the guava decline complex and highlight the role of nursery-borne inoculum in disease spread.